2022
DOI: 10.1038/s41598-022-15048-2
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of trace element content in the lungs of Sao Paulo city residents and its correlation to lifetime exposure to air pollution

Abstract: Heavy metals are natural and essential elements of the environment and living beings, produced from natural (e.g. volcanic activity and cosmic ray-induced spallation) and anthropogenic processes (e.g. industrial and fossil fuel combustion). High-concentrations of heavy metals and radionuclides are also originated from anthropogenic activities in urban and industrial areas. In this preliminary study, we analyzed the levels of heavy metals and Polonium-210 (210Po) in lung tissues in autopsies from residents of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…As typical constituents of fine airborne particles, NPAHs can penetrate deep into the lungs after inhalation where they also accumulate [ 22 , 23 , 24 ]. Consequently, the most pronounced effect on human health is on the respiratory system, causing asthma and allergies [ 25 , 26 ], obstructive pulmonary disease [ 27 ], and even lung cancer [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…As typical constituents of fine airborne particles, NPAHs can penetrate deep into the lungs after inhalation where they also accumulate [ 22 , 23 , 24 ]. Consequently, the most pronounced effect on human health is on the respiratory system, causing asthma and allergies [ 25 , 26 ], obstructive pulmonary disease [ 27 ], and even lung cancer [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it overlooks the analysis of the composition of pigments deposited in the lungs. Although previous studies have already identified and measured the chemical element profile of anthracosis in the lungs of residents in Sao Paulo (Saieg et al, 2011;Dos Santos et al, 2022), it is not possible to relate the health effects associated to anthracosis deposition with a specific compound. Establishing a suitable control group is particularly intricate; however, collected data can be analyzed effectively with statistical support.…”
Section: Pulmonary Anthracosismentioning
confidence: 99%
“…Several anthropogenic sources also emit a variety of potentially toxic trace elements such as As, Cr, Pb, Ni, V, Cd, Co, Zn, and Cu, mostly associated with fine PM (with aerodynamic diameter ≤2.5 μm; PM 2.5 ), which can penetrate deep into the human respiratory tract. Prolonged exposure to these toxic elements through inhalation and/or dermal exposure can lead to several health hazards, including cancer [ [2] , [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%
“…PM-bound trace elements also display size-dependent abundance. Crustal elements such as Ca, Fe, Mg, and Mn are mostly associated with coarser PM fractions (PM 2.5-10 ) [ 2 , 7 , 8 ]. Certain elements, mostly the anthropogenic ones, also display more than one dominant size mode (bimodal, trimodal), indicating a variety of sources for such elements [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%